Performa Bank Syariah: Analisis Kinerja BPRS Kota dan Kabupaten Bekasi Tahun Buku 2022-2023 - Habibah, Inna Imanestia (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2024)
This study aims to analyze the performance of Islamic Banks using the Islamic People's Economic Bank Performance analysis approach. This study takes BPRS objects domiciled in Bekasi City and Regency with the 2022-2023 Fiscal Year published on the website of the Republic of Indonesia Financial Services Authority (OJK). The quantitative method with a descriptive approach is the instrument of this study. The findings of the study indicate that several BPRS banks experienced a decline in performance, while others experienced an increase. This indicates that banks must continue to innovate and develop more effective strategies to face various challenges in the Islamic banking industry. This study suggests increasing operational efficiency, developing more innovative products and services, and increasing the ability to manage risk.